Investigation of Association Between TLR4 Gene Polymorphisms and Osteoporosis in Postmenauposal Turkish Women - Ozkan, Zehra Sema; Deveci, Derya; Yuce, Huseyin (Kowsar Corp, 2012)
Background: Postmenopausal osteoporosis is a systemic bone disease that is characterized by accelerated bone loss after menopause and an increased risk of fractures. The immune system and cytokines regulate bone metabolism. Toll-like receptors (TLRs) play an important role in the induction and regulation of the innate immune system and adaptive immune responses. Objectives: To investigate the association between TLR4 gene polymorphisms and bone mineral density (BMD) in postmenopausal osteoporotic (OP) and nonosteoporotic (NOP) Turkish women. Patients and Methods: The study population consisted of 178 OP and 178 NOP Turkish women. BMDs were obtained by dual-energy X-ray absorptiometry. Two single-nucleotide polymorphisms (SNPs) of the TLR4 gene (Asp299Gly and Thr399Ile) were examined by polymerase chain reaction-restriction fragment length polymorphism. The frequency of polymorphisms and the possible relationships between genotypes and BMD were the main outcome measures. Results: Lumbar BMD of OP women was significantly lower than in NOP women (P = 0.04), but total hip BMD and Z scores did not differ. The frequency of the Asp299Gly and Thr399Ile polymorphisms in our population was 18% and 15%, respectively. There was no significant difference in the frequency of TLR4 gene (Asp299Gly and Thr399Ile) polymorphisms between OP and NOP women, but carriers of heterozygous genotypes had lower BMDs (P < 0.01 and P < 0.01). Conclusions: We observed lower BMDs in carriers of heterozygous genotypes of polymorphisms than homozygous mutant genotypes. With our limited population, no firm conclusions can be drawn as to what extent low bone mineral density is associated with these heterozygous genotypes, and further studies are needed to analyze our results. Copyright (C) 2012 Kowsar M. P. Co. All rights reserved.
Keywords: Bone Mineral Density; Cytokine; Inflammation; Polymorphism; Postmenopausal Osteoporosis; TLR4